The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1002/prot.21857
|View full text |Cite
|
Sign up to set email alerts
|

The protein fluorescence and structural toolkit: Database and programs for the analysis of protein fluorescence and structural data

Abstract: Protein fluorescence is a powerful tool for studying protein structure and dynamics if we have a means to interpret the spectral data in terms of protein structural properties. Our previous research successfully provided this support through the development of individual software modules implementing the algorithms for fluorescence and structural analyses. Now we have integrated the developed software modules, introduced a new program for the assignment of tryptophan residues to spectral‐structural classes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 28 publications
1
38
0
2
Order By: Relevance
“…We previously demonstrated that the emission of tryptophan residues of pHLIP is distinct in each of the three states. In state I (in solution), the tryptophan residues of pHLIP are completely exposed to the polar and flexible water environment, resulting in long wavelength fluorescence, (Class III according to the Burstein and Reshetnyak classification (13,14). In state II (adsorbed to the bilayer surface), tryptophan residues are partially buried in the hydrophobic core of the lipid bilayer, leading to a blue shift of the emission and an increase of intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that the emission of tryptophan residues of pHLIP is distinct in each of the three states. In state I (in solution), the tryptophan residues of pHLIP are completely exposed to the polar and flexible water environment, resulting in long wavelength fluorescence, (Class III according to the Burstein and Reshetnyak classification (13,14). In state II (adsorbed to the bilayer surface), tryptophan residues are partially buried in the hydrophobic core of the lipid bilayer, leading to a blue shift of the emission and an increase of intensity.…”
Section: Resultsmentioning
confidence: 99%
“…At low lipid/peptide ratios the values of coordination number are lower and change from 19 to 6 with increasing temperature. We assume that each peptide helix might be surrounded by the same number of lipids (14) as in the case of high lipid/peptide ratios, but the lipids might be shared between helices (one lipid interacting with two different helices at the same time). However, we cannot exclude the possibility of some helix aggregation at low lipid/peptide ratios.…”
Section: (For 37°c) (B)mentioning
confidence: 99%
“…4) support a similar polar and hydrophobic setting in AgTRPA1 for Trp-779 and Trp-950, respectively. The expected emission maximum for a tryptophan of class III is between 346 and 350 nm, whereas the ranges for tryptophans belonging to classes S and I are blue-shifted to 321-325 and 330 -333 nm (40). Concentration-response experiments show that both constructs have intrinsic tryptophan fluorescence with a maximum at 337 nm, which can be totally quenched by the agonist AITC without any associated shift of the maximum in the spectra (Fig.…”
Section: Intrinsic Tryptophan Fluorescence Ismentioning
confidence: 91%
“…3B). Two conserved tryptophans, corresponding to Trp-779 and Trp-950 in AgTRPA1, are buried in the structure: a classification of these tryptophans in the structure of hTRPA1 using PFAST (Protein Fluorescence and Structure Toolkit (40)) suggests that the former is located in a fairly polar environment (class III, p ϭ 0.87), whereas the latter is packed into more hydrophobic milieu (class S (p ϭ 0.55) or class I (p ϭ 0.45)). The conserved amino acid residues within 5 Å of the two tryptophan indole rings (Fig.…”
Section: Intrinsic Tryptophan Fluorescence Ismentioning
confidence: 99%
“…Steady state tryptophan fluorescence is a useful technique to probe the environment around the aromatic amino acid residues (33,34). Illuminating proteins with 290-nm excitation wavelength selectively excites tryptophan.…”
Section: Conformation and Hydrodynamic Radii Of Wt And Mutantmentioning
confidence: 99%